2012
DOI: 10.3892/mmr.2012.1244
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mitotane on viability, steroidogenesis and gene expression in NCI-H295R adrenocortical cells

Abstract: Mitotane, also known as o,p'‑DDD or (RS)‑1‑chl-oro‑2‑[2,2‑dichloro‑1‑(4‑chlorophenyl)‑ethyl]‑benzene, is an adrenal cortex-specific cytotoxic drug used in the therapy of adrenocortical carcinoma (ACC). The drug also inhibits steroidogenesis, however, the mechanisms of its anticancer and antisteroidogenic effects remain unknown. At present, data on the impact of mitotane on cell viability and the regulation of genes encoding proteins associated with st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
48
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 42 publications
5
48
0
3
Order By: Relevance
“…The level of caspase-3 and -7 increased in the cells. The increased caspase-3 and -7 activities in these cells were also shown by other researchers [28].Theinfluen ceofo,p'-DDD on apoptotic DNA fragmentation in vitro was analyzed in our work [29]. Western blot analysis showed that o,p'-DDD reduced the expression of the mitochondrial anion channel VDAC in the outer membrane, increased the expressionofcaspase-3butdidnotaffectthelevelofsuc-cinate dehydrogenase (complex II) in the mitochondriainnermembrane [23].Theeffectofo,p'-DDD on respiratory chain was studied on cultured H295R and SW13 cells derived from human adrenocortical carcinoma [31].…”
supporting
confidence: 58%
See 1 more Smart Citation
“…The level of caspase-3 and -7 increased in the cells. The increased caspase-3 and -7 activities in these cells were also shown by other researchers [28].Theinfluen ceofo,p'-DDD on apoptotic DNA fragmentation in vitro was analyzed in our work [29]. Western blot analysis showed that o,p'-DDD reduced the expression of the mitochondrial anion channel VDAC in the outer membrane, increased the expressionofcaspase-3butdidnotaffectthelevelofsuc-cinate dehydrogenase (complex II) in the mitochondriainnermembrane [23].Theeffectofo,p'-DDD on respiratory chain was studied on cultured H295R and SW13 cells derived from human adrenocortical carcinoma [31].…”
supporting
confidence: 58%
“…Three steroidogenesis regulatory genes hSd3B1, hSd3B2 and CYP21A2 were underexpressed, and four genes GdF15, ALdh1L2, TRIB3 and SERPINE2 were overexpressed. A decrease in the mRNA level of cytochromes CYP11A1 and CYP17A1 in H295R cells in the presence of o,p'-DDD was shown in the study [28]. o,p'-DDD was found to cause a decrease in the level of mRNA protein kinase A regulatory subunit (PRKAR1A).…”
mentioning
confidence: 84%
“…Z ostatnich badań przedklinicznych wiadomo, że mitotan redukuje przeżywal-ność komórek NCIH295R (ludzka linia komórek ACC) poprzez indukcję apoptozy spowodowaną zwiększe-niem aktywności kaspazy 3 oraz kaspazy 7. Badanie to wykazało, że mitotan znacząco hamuje ekspresję genów biorących udział w steroidogenezie, sekrecji kortyzolu oraz DHEAS [47]. Dokładny mechanizm tego działania w komórkach ludzkich wciąż jest badany.…”
Section: Patogeneza I Aspekty Molekularneunclassified
“…This study indicated that mitotane markedly inhibited the expression of genes involved in steroidogenesis, secretion of cortisol, and DHEAS [47]. In humans, the exact mechanism of its action remains to be fully elucidated.…”
Section: Prace Poglądowementioning
confidence: 99%
“…Mitotane is an isomer of the insecticide DDT with adrenolytic activity. Mitotane inhibits gene expression of a number of enzymes involved in the steroidogenetic pathway in the mitochondria of steroidogenic cells decreasing both plasma and urine hormone levels [135][136][137]. Mitotane produces focal degeneration of the zona fasciculata and the zona reticularis, while the effects on the glomerular area are relatively scarce [138].…”
Section: Mitotanementioning
confidence: 99%